North-South Trade: The Impact of Robotization - Andreas Baur; Lisandra Flach; Isabella Gourevich; Florian Unger (Center for Economic Studies and ifo Institute (CESifo), 2023)
This paper investigates the effect of robotization in high-income countries on firm-level North-South trade along the value chain. Using a novel combination of data sources including firm-level export data, input-output linkages, and robot adoption, we show contrasting implications for Southern firms. Increased exposure to robot adoption in the destination country of exports reduces firm-level exports in case of robot adoption in the same industry. However, the opposite holds when accounting for input-output linkages and trade along the value chain. We outline a North-South trade model with endogenous robot adoption that accounts for the different channels shown in the data. Our findings highlight the importance of taking into account supply chain linkages and suggest net positive effects for Southern exporters.
Keywords: D20; F14; L20; O33; 330; robotization; firm-level trade; value chain linkages; sourcing